Fibrin-Modified Cellulose as a Promising Dressing for Accelerated Wound Healing - Bacakova, Marketa; Pajorova, Julia; Sopuch, Tomas; Bacakova, Lucie (Materials (Basel, Switzerland), 2018)
Dermal injuries and chronic wounds usually regenerate with scar formation. Successful treatment without scarring might be achieved by pre-seeding a wound dressing with cells. We aimed to prepare a wound dressing fabricated from sodium carboxymethylcellulose (Hcel® NaT), combined with fibrin and seeded with dermal fibroblasts in vitro. We fabricated the Hcel® NaT in a porous and homogeneous form (P form and H form, respectively) differing in structural morphology and in the degree of substitution of hydroxyl groups. Each form of Hcel® NaT was functionalized with two morphologically different fibrin structures to improve cell adhesion and proliferation, estimated by an MTS assay. Fibrin functionalization of the Hcel® NaT strongly enhanced colonization of the material with human dermal fibroblasts. Moreover, the type of fibrin structures influenced the ability of the cells to adhere to the material and proliferate on it. The fibrin mesh filling the void spaces between cellulose fibers better supported cell attachment and subsequent proliferation than the fibrin coating, which only enwrapped individual cellulose fibers. On the fibrin mesh, the cell proliferation activity on day 3 was higher on the H form than on the P form of Hcel® NaT, while on the fibrin coating, the cell proliferation on day 7 was higher on the P form. The Hcel® NaT wound dressing functionalized with fibrin, especially when in the form of a mesh, can accelerate wound healing by supporting fibroblast adhesion and proliferation.
Keywords: dermal fibroblasts; skin; wound dressing; sodium carboxymethylcellulose; wound healing; fibrin